Android-Based Learning Media Designed with Figma for Mechanical Measuring Instruments in Vocational Automotive Education - Arga Farid Ahmadi; Setyo Bhahak Fendi Baihaqi; Rizqi Fitri Naryanto (Universitas Negeri Padang, 2026)
Repetitive and conventional learning can make mechanical measuring instrument topics difficult for vocational students to understand. This study developed and initially evaluated Android-based learning media designed with Figma for Mechanical Measuring Instruments. The research used the ADDIE development model with a pre-experimental one-group pretest–posttest design involving Grade X TKRO students. Product feasibility was assessed by media and material experts, while learning outcomes were examined through pretest, posttest, t-test, N-Gain, and student responses. The media expert score was 85.4%, and the material expert score was 90.8%, both in the very feasible category. The average score increased from 43.6 in the pretest to 80.2 in the posttest. The reported t-test value was 44.892 > 2.026, with an N-Gain of 0.67, indicating moderate improvement. Student responses reached 86.5%, categorized as very good.